PERLINDUNGAN HUKUM BAGI KONSUMEN DALAM TRANSAKSI JUAL BELI MELALUI MEDIA SOSIAL - Fitriah, Fitriah (Solusi, 2020)
The very rapid growth of internet users has made the internet a very effective medium for carrying out trading activities. Buying and selling transactions through this media are an attractive alternative and are very attractive to consumers, because it is very easy to find the desired item, can compare prices, payments are simply made by transfer, waiting for goods to arrive without leaving the house, products can be seen 24 hours by anyone and whenever. The validity of electronic contracts carried out by both parties based on the principle of consensualism regulated in Article 1320 of the Civil Code and strengthened by Article 18 of the Electronic Information and Transactions Law, that Electronic transactions that are contained in an Electronic contract are binding on the parties. E-Commerce transactions are in principle the same as other transactions so that if one party defaults to the other party that is contrary to the agreement, it has violated the applicable positive law and also the agreement that has occurred at the beginning of the transaction and civil law action can be taken through the court or through channels. non court.